Fluid balance during and after an Ironman triathlon - Speedy, D. B.; Noakes, T. D.; Kimber, N. E.; Rogers, I. R.; Thompson, J. M.; Boswell, D. R.; Ross, J. J.; Campbell, R. G.; Gallagher, P. G.; Kuttner, J. A. (Clinical Journal of Sport Medicine, 2001)
OBJECTIVE: To record weight changes, fluid intake and changes in serum sodium concentration in ultradistance triathletes. DESIGN: Descriptive research. SETTING: Ironman triathlon (3.8 km swim, 180 km cycle, 42.2 km run). Air temperature at 1200 h was 21 degrees C, (relative humidity 91%). Water temperature was 20.7 degrees C. PARTICIPANTS: 18 triathletes. INTERVENTIONS: None. MAIN OUTCOME MEASURES: Subjects were weighed and had blood drawn for serum sodium concentration [Na], hemoglobin, and hematocrit, pre-race, post-race, and at 0800 h on the morning following the race ("recovery"); subjects were also weighed at transitions. Fluid intake during the race was estimated by athlete recall. RESULTS: Median weight change during the race = -2.5 kg (p < 0.0006). Subjects lost weight during recovery (median = -1.0 kg) (p < 0.03). Median hourly fluid intake = 716 ml/h (range 421-970). Fluid intakes were higher on the bike than on the run (median 889 versus 632 ml/h, p = 0.03). Median calculated fluid losses cycling were 808 ml/h and running were 1,021 ml/h. No significant difference existed between pre-race and post-race [Na] (median 140 versus 138 mmol/L) or between post-race and recovery [Na] (median 138 versus 137 mmol/L). Plasma volume increased during the race, median + 10.8% (p = 0.0005). There was an inverse relationship between change in [Na] pre-race to post-race and relative weight change (r = -0.68, p = 0.0029). Five subjects developed hyponatremia ([Na] 128-133 mmol/L). CONCLUSIONS: Athletes lose 2.5 kg of weight during an ultra-distance triathlon, most likely from sources other than fluid loss. Fluid intakes during this event are more modest than that recommended for shorter duration exercise. Plasma volume increases during the ultradistance triathlon. Subjects who developed hyponatremia had evidence of fluid overload despite modest fluid intakes.